The Contributions of Video-Analysis in Early Childhood Education and Care Research - Migliarini, Valentina; Lazzari, Arianna; Balduzzi, Lucia; de Mets, Jan; Slusarczyk, Magdalena (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2019)
This paper presents a review of the literature on the use of video-analysis in Early Childhood Education and Care (ECEC) contexts. The purpose of conducting such review emerged from the needs of exploring possibilities and limitations of video-analysis as a research mediational tool in ECEC services, especially in a European context. Constituting an integral task of a larger study funded by the Erasmus + grant program, and titled Transition Children and Kindergarten, this review considers English language studies and studies written in the language of the project partner countries (i.e. Italy, Poland, and Belgium/Flanders). The narrative synthesis of the studies considered develops around three emerging areas in which video-analysis in ECEC has been used already, namely: (1) teachers/parents/community’s reflection, consciousness and empowerment; (2) diversity and inclusion; (3) interaction children-educator. The paper ends with a final conclusion on the relevance of video-analysis for ECEC practitioners’ professional development and collaborative growth.